2009
DOI: 10.1248/bpb.32.1335
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Protects Mesenchymal Stem Cells against Hypoxia-Induced Apoptosis in Vitro

Abstract: Bone marrow mesenchymal stem cells (MSCs) have the potential to be used in the cellular therapy of solid organs. However, tissue regeneration is limited by the death of transplanted cells. One of the main mechanisms of stem cell death in transplanted organs is through ischemia. In the present study, we sought to investigate whether a plant-derived antioxidant, berberine (BBR), could protect MSCs against MSCs apoptosis in a model of ischemia consisting of serum deprivation-and hypoxia-induced apoptosis in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…Although we did not detect the SR expression in our experiments, a previous study has proven that berberine could induce SR-A expression in macrophages [43]. Additionally, berberine could scavenge the reactive oxygen species (ROS) and inhibit the c-jun NH (2)-terminal kinase (JNK), the loss of mitochondrial membrane potential and the release of cytochrome c (Cyt C) and caspase-3 [44]. In our study, Aldo-treated rats showed a high glomerular ROS production marker (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Although we did not detect the SR expression in our experiments, a previous study has proven that berberine could induce SR-A expression in macrophages [43]. Additionally, berberine could scavenge the reactive oxygen species (ROS) and inhibit the c-jun NH (2)-terminal kinase (JNK), the loss of mitochondrial membrane potential and the release of cytochrome c (Cyt C) and caspase-3 [44]. In our study, Aldo-treated rats showed a high glomerular ROS production marker (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…A decrease in activity of the antioxidant enzyme catalase, a major metaboliser of ROS, without changes in SOD and SOD subunit levels confirmed that the metabolism of ROS was also impaired (or at least not sufficient) [Peterson et al, 2011]. Furthermore, short hypoxic exposure of ambient O 2 -expanded MSCs provoked a decrease in the mitochondrial transmembrane potential [Zhu et al, 2006;Zhang et al, 2009;Nie et al, 2011], cytochrome C release into the cytoplasm [Zhu et al, 2006;Zhang et al, 2009] and a decrease in intracellular ATP [Chang et al, 2009;Deschepper et al, 2011].…”
Section: Discussionmentioning
confidence: 82%
“…Some authors consider short-term hypoxic exposure of MSCs to be permanently maintained under ambient O 2 (20%) as oxidative stress, which may cause functional impairment due to increased ROS production [Guzy and Schumacker, 2006;Zhang et al, 2009;Busletta et al, 2011;Peterson et al, 2011] in part triggered by a significant increase in prooxidants, such as the ROS producer NAD(P)H oxidase subunits p67phox and p47phox [Peterson et al, 2011]. A decrease in activity of the antioxidant enzyme catalase, a major metaboliser of ROS, without changes in SOD and SOD subunit levels confirmed that the metabolism of ROS was also impaired (or at least not sufficient) [Peterson et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…There is an integrated system of clearing ROS in the body to keep balance. Oxidation of cell membrane phospholipids, enzyme, and DNA [24][25][26][27] by high levels of ROS can alter function of signal transduction, platelet aggregation, immune control, and the regulation of cell growth, and they can also cause necrosis or apoptosis [28][29][30][31]. As the generation of ROS is the result of disordered functioning of mitochondria and metabolite augmentation, there may be ways to regulate ROS selectively in cancer cells [12,32].…”
Section: Discussionmentioning
confidence: 99%